Determinan Ekspor Minyak Mentah Indonesia ke Singapura - Djohan, Yusuf; Ervani, Eva (PPJP ULM, 2025)
This study aims to analyze the factors influencing Indonesia’s crude oil export performance to Singapore by employing the Autoregressive Distributed Lag (ARDL) approach. The dataset covers the period 1995–2024 and is compiled from international and national sources, including the United Nations Comtrade, World Bank, International Energy Agency (IEA), and Indonesia’s Ministry of Energy and Mineral Resources (ESDM). The variables examined include world oil prices, Singapore’s Gross Domestic Product (GDP), oil refinery throughput, Foreign Direct Investment (FDI), domestic oil production, and a global crisis dummy. The estimation results indicate that in the long run, world oil prices, Singapore’s GDP, and domestic oil production have positive and significant impacts on Indonesia’s crude oil exports, whereas refinery throughput in Singapore and global crises exhibit significant negative effects. Meanwhile, FDI shows no significant impact in the short run, although it has the potential to enhance export capacity over longer horizons. The short-run dynamics also reveal that nearly 60 percent of disequilibrium is corrected annually, confirming a strong error correction mechanism. This study contributes by highlighting the interplay between domestic capacity and external shocks, offering policy insights for strengthening Indonesia’s energy export resilience.